Dietary nitrate supplementation does not improve cycling time-trial performance in the heat - Kent, G. L.; Dawson, B.; Cox, G. R.; Burke, L. M.; Eastwood, A.; Croft, K. D.; Peeling, P. (Journal of Sports Sciences, 2018)
This investigation examined the effect of beetroot juice (BR) supplementation, a source of dietary nitrate (NO3-), on cycling time-trial (TT) performance and thermoregulation in the heat. In a double-blind, repeated-measures design, 12 male cyclists (age 26.6 ± 4.4 years, VO2peak 65.8 ± 5.5 mL/kg.min) completed four cycling TTs (14 kJ/kg) in hot (35°C, 48% relative humidity) and euthermic (21°C, 52%) conditions, following 3 days supplementation with BR (6.5 mmol NO3- for 2 days and 13 mmol NO3- on the final day), or NO3-depleted placebo (PLA). Salivary NO3- and nitrite, core (Tc) and mean skin temperature (Tsk) were measured. Salivary NO3- and nitrite increased significantly post-BR supplementation (p < 0.001). Average TT completion time (mm:ss) in hot conditions was 56:50 ± 05:08 with BR, compared with 58:30 ± 04:48 with PLA (p = 0.178). In euthermic conditions, average completion time was 53:09 ± 04:35 with BR, compared with 54:01 ± 04:05 with PLA (p = 0.380). The TT performance decreased (p < 0.001), and Tc (p < 0.001) and Tsk (p < 0.001) were higher in hot compared with euthermic conditions. In summary, BR supplementation has no significant effect on cycling TT performance in the heat.